Impact of a web-based personally tailored physical activity intervention on depression, anxiety, stress and quality of life: Secondary outcomes from a randomized controlled trial. (October 2022) - Vandelanotte, Corneel; Duncan, Mitch J.; Plotnikoff, Ronald C.; Rebar, Amanda; Alley, Stephanie; Schoeppe, Stephanie; To, Quyen; Mummery, W. Kerry; Short, Camille E.
Abstract: Background: Few studies have investigated the impact of web-based physical activity interventions on mental health outcomes. Therefore, this study examined the impact of a web-based personally tailored physical activity intervention on depression, anxiety, stress and quality of life. Methods: 501 participants were randomised into either a control group or a pooled intervention condition who received a 3-month web-based personally tailored physical activity intervention. Previously, this intervention has demonstrated to improve self-reported physical activity, but not device-measured physical activity. At baseline, 3- and 9-months, depression, anxiety and stress were assessed using the DASS21, and quality of life was assessed using the SF-12V2. General linear mixed models examined differences between groups over time. Results: Most participants (>80%) reported normal levels of depression, anxiety or stress. Relative to baseline levels, significant reductions of depression, anxiety, stress and the SF12 mental health component were observed in the pooled intervention group at 3 and 9 months. Relative to the control group, significant reductions were observed in the pooled intervention group for depression and stress (3-months only) and anxiety (3- and 9-months), but not quality of life. Conclusion: A web-based physical activity intervention can result in positive mental health outcomes, even in the absence of device-measured physical activity improvements. However, these findings need to be confirmed in future studies. Trial registration number: ACTRN12615000057583. Highlights: The web-based intervention was able to improve depression, anxiety and stress. The web-based physical activity intervention had little impact on quality of life. Mental health outcomes improved even when device-measured physical activity did not.